2011
DOI: 10.1108/13552551111158826
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how perceived barriers influence growth intentions and behaviours

Abstract: PurposeThis paper aims to expand on existing conceptualisations of barriers to small business growth by addressing the question of how, or in what ways, do perceived barriers influence the growth intentions and behaviours of owner‐managers?Design/methodology/approachAdopting an interpretive methodological approach, in‐depth semi‐structured interviews were held with 27 owner‐managers working in St Petersburg, Russia. Participants were asked about their intentions for their businesses, how they intended to grow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 66 publications
1
29
0
1
Order By: Relevance
“…We discovered that institutions appear to operate in different ways in relation to how they are perceived by founder-CEOs to influence their intentions and behaviour. Thus the main findings of our study extend the knowledge body on perceived institutional barriers in the Russian context (Doern, 2011;Pissarides et al, 2003).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We discovered that institutions appear to operate in different ways in relation to how they are perceived by founder-CEOs to influence their intentions and behaviour. Thus the main findings of our study extend the knowledge body on perceived institutional barriers in the Russian context (Doern, 2011;Pissarides et al, 2003).…”
Section: Resultssupporting
confidence: 84%
“…Previous research indicated that subjective opinions or 'reality-as-perceived' by the business owners and managers has an influence on both growth motivation and direct behaviour (Davidsson, 1991;Delmar and Wiklund, 2008;Doern, 2009;2011). Theoretical support for the effect of perceptions on actual behaviour is an integral part of institutional theory (North, 1990), and there is empirical evidence of relationships between perceived formal and informal barriers to business operations and a firm's growth in emerging economies (Aidis, 2005;Hashi, 2001;Pissarides et al, 2003).…”
Section: Institutions In Emerging Economiesmentioning
confidence: 99%
“…In particular, literature knows very little about the characteristics of growing firms, which are main drivers of employment growth (Hölzl 2009). Entrepreneurs' growth-orientation in empirical research is very important from the policy angle as few small firms intent to grows, and therefore it provides limited contribution to the economy and therefore questioning the start-up support policies (Santarelli and Vivarelli 2007;Shane 2009;Doern 2011;Román et al 2013). Studies on transition context usually overemphasis institutional environment at the expense of the internal factors such as firm, strategy and management factors (Krasniqi 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Assumptions that small firms or SMEs are considered "scaled-down" versions of a large firm have been successfully challenged in the literature, and there is widespread acceptance that small businesses are not just "little big businesses" (Hill et al, 2002). SMEs have their own particular characteristics that affect the way they operate (Doern, 2012;Filley and Aldag, 1988;Kohtamakii et al, 2012;Kwong, Jones-Evans and Thompson, 2012;Roper and Scott, 2009;Tierney et al, 2012). This supports the assertion that the unique characteristics of the SME require existing organisational sustainability models to be revisited to take cognisance of the particular context and circumstances in which such firms operate.…”
Section: Introductionmentioning
confidence: 99%